MET Exon 14 Variants in Non-Small Cell Lung Carcinoma: Prevalence, Clinicopathologic and Molecular Features - Lisi Yuan; Harshita Mehrotra; Xin He; David Bosler (MDPI AG, 2023)
Somatic MET exon 14 skipping mutations (MET ex14) are targetable driver mutations for non-small cell lung cancer (NSCLC), responsive to MET inhibitors. Objective: This study seeks to further characterize the clinicopathologic features and mutational profile of MET ex14 variant NSCLC. Design: Retrospective review of all MET ex14 tested NSCLC. Testing for selected BRAF, EGFR, HER2, KRAS, and MET mutations was performed using a clinically validated NGS assay, followed by MiSeq sequencing. Variants were classified as significant (Tier1/2) or variants of uncertain significance (VUS) per 2017 AMP/ASCO/CAP Joint Consensus Guidelines. PD-L1 expression was assessed by immunohistochemistry. Results: Of 2296 NSCLCs tested between 2017-7/2019, MET ex14 variants were present in 44 (1.9%). A total of 32 of 44 variants were MET exon 14 skipping, while the other 12 mutations were significant missense (3) or VUS (9). Of nine VUS, five were adjacent to the canonical splice site and likely to impact splicing. Four cases had concomitant mutations. Of 35 cases with known clinical staging, stage 1-2 = 20 (57%), stage 3 = 3 (9%), and stage 4 = 12 (34%). Of 19 resected NSCLSs, histological types and growth pattern included 7 lepidic pattern-predominant. A high percentage of tumors with MET ex14 mutations are positive for PD-L1, and the percentage of cases with PD-L1 expression >50% trends higher in more advanced disease. Conclusions: Most MET variants identified in our cohort (73%) are MET ex14 skipping. The prevalence of MET ex14 variants is 1.9%, and a large percentage of tumors has lower clinical stage and less aggressive pathologic features.